2010
DOI: 10.1523/jneurosci.3177-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Mesolimbic Dopamine Neurons in the Brain Reward Circuit Mediate Susceptibility to Social Defeat and Antidepressant Action

Abstract: We previously reported that the activity of mesolimbic dopamine neurons of the ventral tegmental area (VTA) is a key determinant of behavioral susceptibility vs resilience to chronic social defeat stress. However, this was based solely on ex vivo measurements, and the in vivo firing properties of VTA dopamine neurons in susceptible and resilient mice, as well as the effects of antidepressant treatments, remain completely unknown. Here, we show that chronic (10 d) social defeat stress significantly increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
352
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(389 citation statements)
references
References 27 publications
33
352
0
4
Order By: Relevance
“…My studies utilized the well-established social defeat stress mouse model of depression. An increase in the firing rate and bursting events was found in the VTA DA neurons of the brain reward circuitry in susceptible mice, but not in the resilient subgroup ( 16,17). Our work further showed that this hyperactivity was causally linked to the susceptible pehonotype ( 18,19).…”
supporting
confidence: 61%
“…My studies utilized the well-established social defeat stress mouse model of depression. An increase in the firing rate and bursting events was found in the VTA DA neurons of the brain reward circuitry in susceptible mice, but not in the resilient subgroup ( 16,17). Our work further showed that this hyperactivity was causally linked to the susceptible pehonotype ( 18,19).…”
supporting
confidence: 61%
“…34 The neuronal circuits that underpin stress effects are complex and far from being understood, but an increasing body of literature strongly supports a pivotal role of the DA reward system. 23,24,26,34 SD triggers pronounced increases in VTA DA neuron spontaneous activity, which is causally associated with anhedonia and social aversion. Pre-exposure to stress is also well acknowledged to facilitate self-administration and precipitate relapse, and this is proposed to rely on changes of VTA DA neurons activity.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Chronic social defeat stress (SD) parses the enduring behavioral abnormalities induced by stress and is believed to capture features of depressive-like states. 22 SD triggers an increase in DA VTA neuronal activity 23 that drives social avoidance. DA cells exhibit two distinct patterns of in vivo activity-a low-frequency tonic firing and a high-frequency phasic firing-with the possibility of switching amongst these modes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the attenuation of the mesocortical dopaminergic pathway, it has been shown that repeated social defeat stress increases firings of VTA dopamine neurons for at least several weeks after the last defeat episode (17,18). This increased excitability is accompanied by augmented Ih currents through hyperpolarizationactivated cyclic nucleotide gated (HCN) channels (18).…”
Section: Distinct Functions Of the Mesocortical And Mesoaccumbal Dopamentioning
confidence: 99%
“…This increased excitability is accompanied by augmented Ih currents through hyperpolarizationactivated cyclic nucleotide gated (HCN) channels (18). Local infusion of HCN-channel blocker at one week following the last defeat episode ameliorates depressive behaviors such as social avoidance and reduced sucrose consumption (18).…”
Section: Distinct Functions Of the Mesocortical And Mesoaccumbal Dopamentioning
confidence: 99%